Impact of mutagenesis and lateral gene transfer processes in bacterial susceptibility to phage in food biocontrol and phage therapy - López-Pérez, Júlia; Otero, Jennifer; Sánchez-Osuna, Miquel; Erill, Ivan; Cortés, Pilar; Llagostera, Montserrat (Frontiers in cellular and infection microbiology, 2023)
Introduction: The emergence of resistance and interference mechanisms to phage infection can hinder the success of bacteriophage-based applications, but the significance of these mechanisms in phage therapy has not been determined. This work studies the emergence of Salmonella isolates with reduced susceptibility to a cocktail of three phages under three scenarios: i) Salmonella cultures (LAB), ii) biocontrol of cooked ham slices as a model of food safety (FOOD), and iii) oral phage therapy in broilers (PT).Methods: S. Typhimurium ATCC 14028 RifR variants with reduced phage susceptibility were isolated from the three scenarios and conventional and molecular microbiology techniques were applied to study them.Results and discussion: In LAB, 92% of Salmonella isolates lost susceptibility to all three phages 24 h after phage infection. This percentage was lower in FOOD, with 4.3% of isolates not susceptible to at least two of the three phages after seven days at 4°C following phage treatment. In PT, 9.7% and 3.3 % of isolates from untreated and treated broilers, respectively, displayed some mechanism of interference with the life cycle of some of the phages. In LAB and FOOD scenarios, resistant variants carrying mutations in rfc and rfaJ genes involved in lipopolysaccharide synthesis (phage receptor) were identified. However, in PT, the significant decrease of EOP, ECOI, and burst size observed in isolates was prompted by lateral gene transfer of large IncI1 plasmids, which may encode phage defense mechanisms. These data indicate that the acquisition of specific conjugative plasmids has a stronger impact than mutagenesis on the emergence of reduced phage-susceptibility bacteria in certain environments. In spite of this, neither mechanism seems to significantly impair the success of Salmonella biocontrol and oral phage therapy.